PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS X MATA PELAJARAN DASAR KOMPETENSI KEJURUAN DI SMK BHINEKA KARYA SURAKARTA TAHUN AJARAN 2014/2015 - Cahyadi, Nurido (Jurnal Nosel, 2015)
The objectives of this research are to improve the learning activeness and result in the subject matter of Basic Vocational Competency of the students in Grade X of Bhineka Karya Vocational High School of Surakarta in Academic Year 2014/2015 through the application of the cooperative learning model of the Learning Together type.  This research used the classroom action research with two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. The subjects of research were the students in Grade X of Mechanical Engineering B of the aforementioned school. The data sources of research were the students, observation sheet of learning activeness, and result of learning achievement test. The data of research were validated by using the content validity for the test data and the construct validity for the non-test data. They were analyzed by using the descriptive comparative analysis. The procedure of research consisted of a series of four repeatedly cyclical activities.The application of the cooperative learning model of the Learning Together type can improve the learning activeness and result in the subject matter of Basic Vocational Competency of the students in Grade X of  SMK Bhineka Karya Vocational High School of Surakarta. In the pre-cycle, the percentage of the students who had the expected learning activeness is 40 %. Following the application of the cooperative learning model of the Learning Together type, it becomes 63.34 % in Cycle I and 83.34% in Cycle II respectively. In addition, in the pre-cycle the percentage of the students who fulfilled the minimum learning completeness criterion is 43.34%. Following the application of the cooperative learning model of the Learning Together type, it becomes 76.67 % in Cycle I and 86.67% in Cycle II respectively.